Mayoral candidate characteristics in the state of Baden-Wuerttemberg: Documentation and codebook - Marc-Daniel Moessinger; Mustafa Yeter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
This database was created in the context of the project "Ämterwettbewerb, Qualitiät von Politikern und fiskalische Performance - Eine empirische Analyse deutscher Kommunen", running from September 2012 until February 2015. The project members gratefully acknowledge the financial support from the Fritz Thyssen foundation (project number 10.12.1.094). The database comprises detailed information on the personal characteristics of candidates at mayoral elections in the German state of Baden-Wuerttemberg for the period 1973-2010. In total, 2,442 mayoral candidates from 1,184 mayoral elections are included.
urn:nbn:de:bsz:180-madoc-432235
Keywords: 330